Treatment options for secondary osteonecrosis of the knee in young adults (Systematic review and meta-analysis) - Vinay Joseph; Joseph Boktor; Stefan Bajada; Ben Coupe (Journal of Orthopaedic Reports)
Introduction: Secondary osteonecrosis of the knee affects younger population and has bilateral and extensive lesions. There is lack of evidence and a systematic review of literature on the treatment options is warranted. We aimed at identifying and analysing treatment options for secondary osteonecrosis. Methods: A systematic review of literature was performed in accordance with the Cochrane handbook and reported according to the PRISMA guidelines. Analysis was performed using strategy of proportional meta-analysis. Results: A total of six studies were included with data on 240 knee joints in 192 patients were analysed. Follow up period ranged from 1 to 16 years. The mean age was 34.7. Three studies were on arthroplasty and three on joint preserving interventions. Steroid induced osteonecrosis was the majority. The pooled analysis showed an improvement of pre-operative knee score from 50.47 to 89.21 post-operatively. The pooled effect size for failure rate was 8.7 % in joint preserving interventions and 9.2 % in joint replacement group. Conclusion: Secondary knee osteonecrosis poses a therapeutic dilemma especially in early stages of osteonecrosis. Both joint preserving and joint replacement interventions do not show any significant or unacceptable complications. The results of this study will aid clinicians in the shared decision making process.